Trans Justice Fights Trans Moral Panic - Mestre i Mestre, Ruth M. (The Age of Human Rights Journal, 2022)
Between the summer of 2019 and the summer of 2021, a violent discussion about trans rights took place in Spain. This paper argues that the discussion can be understood as an instance of ‘social problems work’, more specifically as part of a moral crusade or a moral panic episode. Implicit in this is the idea that there has been an over-reaction to trans recognition and trans equality laws, publicly presented as a major social problem. This paper also provides legal arguments against the fears voiced in the discussion, by summarizing relevant ECHR case-law that agrees with an alternative feminist account of trans rights that de-pathologizes gender-identity self-determination. The paper thus suggests that a ‘cultural war’ over gender identity has been ignited and has yet to be fully fought and won.